2022
DOI: 10.4028/p-70fh65
|View full text |Cite
|
Sign up to set email alerts
|

Cutting Forces Impact on the Spindle Path during Robotic Milling

Abstract: Offline programming is a critical step in the implementation of various robotic tasks such as pick-and-place, welding, cutting, and milling. This paper describes a simulation study that analyses the accuracy of the robot's path tracking, during tasks that require the robot tool to interact with the environment, while considering the current operating conditions. To accurately determine the actual position of the Tool Center Point (TCP) and the associated orientation of the end effector, the study will first es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
0
0
Order By: Relevance
“…To predict the tool / material interaction when simulating robotic machining, the milling process must be accurately modelled. The method presented in [38] is sufficient to simulate the total and average cutting force required for the desired operation. The tool geometry and cutting conditions used in this study are shown in table 3.…”
Section: Application To Shoulder Milling Operationmentioning
confidence: 99%
“…To predict the tool / material interaction when simulating robotic machining, the milling process must be accurately modelled. The method presented in [38] is sufficient to simulate the total and average cutting force required for the desired operation. The tool geometry and cutting conditions used in this study are shown in table 3.…”
Section: Application To Shoulder Milling Operationmentioning
confidence: 99%